Định hướng phát triển và liên kết vùng tại Việt Nam giai đoạn 2026‒2030, tầm nhìn 2045 - Nguyễn Kim , Đức; Nguyễn Đông , Phong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study delineates strategic orientations for optimizing regional development and interregional linkages in Vietnam, aimed at enhancing the role of regions in the nation’s socio-economic development and position them as dynamic and sustainable growth hubs. The proposed framework is grounded in three key components: (1) a comprehensive review of global regional development models, (2) an examination of the perspectives of the Party and the State regarding regional development in Vietnam, and (3) a systematic analysis of socio-economic constraints across six regions to identify structural bottlenecks and formulate targeted policy recommendations. This study seeks to strengthen Vietnam’s overall economic resilience and long-term growth trajectory by emphasizing regional integration and sustainable development.
Keywords: Regional development; Interregional linkages; Socio-economic development